Transaksi Bisnis Game Axie Infinity di Bungkal Perspektif Etika Bisnis Islam - Mevianti Nur Rahma; Ely Masykuroh; Amin Wahyudi (Journal of Economics, Law, and Humanities, 2023)
Online games that carry the theme of the play-to-earn movement have become a new phenomenon in the game industry because they can be used for a business. One of the games that developed into a business is the Axie Infinity game. The research method is a qualitative descriptive, field research approach with data obtained from interview data collection and documentation. The results of this study are 1) The practice of Axie Infinity game business transactions is carried out in two ways, namely through the Axie Infinity marketplace and through the intermediary of the Axie Family community leader. Both ways of business transactions are contrary to the principles or axioms of Islamic business ethics, which are not in accordance with the principles of tawhid, balance or justice, free will, and responsibility. 2) Factors that affect the business transactions of the Axie Infinity game include interpretation factors of the law, organizational factors, and individual factors or certain condition situations. 3) The play of Axie Infinity game done by players has an impact on the game players. Impact can be in the form of impacts on economic, social, impact on physical health, psychological aspects, time aspects, and financial aspects. In general, the business does have an impact on increasing player income, but the income obtained is erratic and risks player losses.